Experimental investigation on heating performance of heat pump for electric vehicles at −20 °C ambient temperature. (15th September 2015) - Qin, Fei; Xue, Qingfeng; Albarracin Velez, Giovanny Marcelo; Zhang, Guiying; Zou, Huiming; Tian, Changqing
Highlights: An ASHP system with refrigerant injection for EVs is designed, for cold regions. The heat performances of the system are tested at −20 °C ambient temperature. The system cycle process with refrigerant injection are analyzed on lgP-H diagrams. The effects of refrigerant injection, dryness, and in-car inlet state are discussed. The new system can improve heating and own better application prospect. Abstract: Since the performance of conventional air source heat pump (ASHP) for electric vehicles (EVs) is apt to decline sharply in low ambient temperature, it will consume more electricity of the cell, and affect driving mileage in cold regions. Aiming at developing high efficiency heating system for EVs in cold regions, an ASHP system applying refrigerant injection for EVs is designed, as well as the test bench is built to investigate its performance. According to the operation condition of EVs, heating performances are tested on different in-car inlet air temperature and various fresh air ratios under −20 °C ambient temperature. The system cycle process with refrigerant injection, as well as the influences of refrigerant injection and dryness are also analyzed and discussed. The results show that the heating capacity of the ASHP with refrigerant injection can be increased up to 31%, and in comparison with the conventional heat pump system its heating performance is better when in-car inlet temperature is above −10 °C. Therefore, ASHP with refrigerant injection has great potentiality to be applied for the EVs in cold regions.